Preparation and antimicrobial action of three tryptic digested functional molecules of bovine lactoferrin. - Nilisha Rastogi; Nitish Nagpal; Hammad Alam; Sadanand Pandey; Lovely Gautam; Mau Sinha; Kouichirou Shin; Nikhat Manzoor; Jugsharan S Virdi; Punit Kaur; Sujata Sharma; Tej P Singh (PLoS ONE, 2014)
Lactoferrin is an 80 kDa bilobal, iron binding glycoprotein which is primarily antimicrobial in nature. The hydrolysis of lactoferrin by various proteases in the gut produces several functional fragments of lactoferrin which have varying molecular sizes and properties. Here, bovine lactoferrin has been hydrolyzed by trypsin, the major enzyme present in the gut, to produce three functional molecules of sizes approximately 21 kDa, 38 kDa and 45 kDa. The molecules have been purified using ion exchange and gel filtration chromatography and identified using N-terminal sequencing, which reveals that while the 21 kDa molecule corresponds to the N2 domain (21LF), the 38 kDa represents the whole C-lobe (38LF) and the 45 kDa is a portion of N1 domain of N-lobe attached to the C-lobe (45LF). The iron binding and release properties of 21LF, 38LF and 45LF have been studied and compared. The sequence and structure analysis of the portions of the excision sites of LF from various species have been done. The antibacterial properties of these three molecules against bacterial strains, Streptococcus pyogenes, Escherichia coli, Yersinia enterocolitica and Listeria monocytogenes were investigated. The antifungal action of the molecules was also evaluated against Candida albicans. This is the first report on the antimicrobial actions of the trypsin cleaved functional molecules of lactoferrin from any species.